Activated monocytes and markers of inflammation in newly diagnosed multiple sclerosis. Issue 7 (5th May 2020) - Carstensen, Mikkel; Christensen, Tove; Stilund, Morten; Møller, Holger J; Petersen, Eva L; Petersen, Thor
Abstract: In multiple sclerosis (MS), the inflammation and demyelination of the central nervous system (CNS) develop in distinct ways. This makes diagnosing patients difficult, imperative to initiating early and proper treatment. Several common features exist, among them a profound infiltration of monocytes into the CNS mediating demyelination and tissue destruction. In the periphery, monocytes are divided into three subsets depending on expression of CD14 and CD16, representing different stages of activation and differentiation. To investigate their involvement in MS, peripheral blood mononuclear cells (PBMCs) from 61 patients with incipient, untreated MS and 22 symptomatic control (SC) patients as well as 6 patients with radiologically isolated syndrome (RIS) were characterized ex vivo . In addition, paired serum and cerebrospinal fluid (CSF) samples were analyzed with a panel of biomarkers. In PBMC samples, we demonstrate decreased levels of nonclassical monocytes with a concomitant significant decrease of human endogenous retrovirus (HERV) H3 envelope epitopes on this monocyte subset compared with SC and RIS. The observed HERV expression is present on nonclassical monocytes irrespective of MS and thus presumably a result of the inflammatory activation. For the other surface markers analyzed, we found significantly decreased expression between classical and nonclassical monocytes. In matched samples of CSF a highly significant increase in levels of soluble markers of activation and inflammation is shown, and notably this is not the case for the serum samples. Of the soluble markers investigated, interleukin (IL)‐12/IL‐23p40 had the highest discriminatory power in differentiating patients with MS from SC and RIS, almost comparable to the immunoglobulin G index. Abstract : Characterizing monocyte subsets in newly diagnosed multiple sclerosis (MS) contributes valuable insight into disease mechanisms and potential therapeutic targets. We present evidence of inflammation‐driven activation of monocytes in peripheral blood as well as detailed analysis of biomarker panels capable of differentiating MS from symptomatic controls.